Overview of µSR Study in Water and Ice (Journal of Nepal Physical Society, 2021)
Muon spin rotation, relaxation and resonance (µSR) method has been used to understand the properties of materials and life. In order to apply the µSR method to life sciences, it is first of all necessary to know the behavior of the muon and its species in different phases of water. In water, muon in diagmetic form is found around 60%, muonium around 20% and remaining missing fraction however in ice, muon and muonium are found almost 50-50% of the incident muon. In ice, the spin dipole interaction of muon with protons will help to understand µSR in water and finally in biosamples.